THE RELATIONSHIP BETWEEN TRIAGE ACCURACY AND SERVICE RESPONSE TIME IN THE EMERGENCY ROOM (IGD) AT RSIA BUNDA JAKARTA IN 2023 - Sari, Ade Malia; Kusnanto, Kusnanto (HEARTY, 2024)
Background: RSIA Bunda Jakarta’s medical record data in 2022 saw an average of 60% of emergency room visits, and in 2023 it will increase to 84%. Emergency Room (ER) nurses and doctors have a very big role and responsibility, namely carrying out triage of patients who will be admitted to the ER. Apart from that, the speed and accuracy of response time in providing assistance to patients greatly determines patient treatment. Purpose: Knowing the relationship between triage accuracy and service response time in the Emergency Room. Methods: Analytical with cross sectional design. The sample in this study was all 30 health workers working in the emergency room at RSIA Bunda Jakarta in January 2024. The sampling technique uses total sampling. Results: The frequency distribution of triage accuracy is mostly appropriate (76,6%) and the response time of nurses and doctors in the ER is mostly correct (80,0%). There is a relationship between the accuracy of triage and the response time of emergency services at RSIA Bunda Jakarta (p value 0,001). Conclusion: There is a relationship between the accuracy of triage and the response time of emergency services. It is hoped that health workers on duty in the emergency room can improve services in accordance with hospital standards so that triage accuracy and fast response time can be created.